Dry matter yield and nodulation of common bean as influenced by phosphorus, lime and compost application at Southern Ethiopia - Shanka, Dereje; Dechassa, Nigussie; Gebeyehu, Setegn; Elias, Eyasu (Walter de Gruyter GmbH, 2018)
Soil acidity is among the major limiting factors for common bean nodulation and productivity. Therefore, field experiments were conducted to investigate the effects of the application of phosphorus (P), lime, and compost on nodulation and dry-matter accumulation of common bean under field conditions at Areka during the long rainy season (belg) and short rainy season (meher). Three rates of compost (0, 5 and 10 t ha-1), three rates of lime (0, 0.64 and 1.28 t ha-1) and three rates of phosphorus (0, 23 and 46 kg P2O5 ha-1) were laid out as a randomized complete block design in a factorial arrangement and replicated three times. All data on nodulation and aboveground drymatter were collected. Results showed that the combined application of P at rates of 46 kg P2O5 ha-1 and lime at rates of 1.28 t ha-1 resulted in the maximum number of total and effective nodules during the long rainy season. Similarly, application of the highest rates of compost along with the highest rates of lime increased the aboveground dry biomass yield significantly over the control during both seasons. Finally, it can be concluded that the application of compost, lime and phosphorus can boost biomass accumulation and nodulation of common bean in acid soils.